Ancient Lamps in the J. Paul Getty Museum - Wohl, Birgitta, 1934-; Bussiere, Jean (Book collections on Project MUSE., 2017)
"An examination of the hundreds of ancient lamps in the J. Paul Getty Museum collection that are made from clay, bronze, and stone, and date from the end of the 6th century BC to the 7th century AD"--Provided by publisher.